ALGORITHMIC TRANSPARENCY AND THE AGE OF DIGITAL SOPHISTS: CHALLENGES FOR PARTICIPATORY DEMOCRACY (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
The article critically analyzes the relationship between algorithmic transparency and participatory democracy, in light of the growing role of artificial intelligence in mediating the digital public space. It starts from the hypothesis that the opacity of algorithms compromises democratic deliberation by favoring the dissemination of persuasive and polarizing discourses—a phenomenon that the study identifies as a contemporary expression of “digital sophists.” The research adopts a deductive methodology and qualitative approach, based on an interdisciplinary literature review that integrates Law, Philosophy, Political Science, and Technology, as well as a comparative study between the regulatory frameworks of the European Union and Brazil. It is found that the absence of algorithmic transparency transfers communicative power from the public sphere to automated systems guided by engagement and monetization logic, undermining informational plurality and citizen autonomy. On the international scene, the progress of the European AI Act stands out as a benchmark for ethical and responsible regulation of artificial intelligence. In Brazil, although the Civil Rights Framework for the Internet and the General Data Protection Law represent advances, they still lack effectiveness and specific mechanisms for algorithmic governance. It is concluded that the consolidation of participatory democracy in the digital age requires public policies focused on informational transparency, platform accountability, and critical education for the use of technology, in order to ensure that artificial intelligence serves freedom and truth, and not discursive manipulation.Keywords: Algorithmic transparency. Participatory democracy. Artificial intelligence. Digital sophists.